Prenatal diagnosis of Galen vein aneurysm: when to deliver? - Assaad Kesrouani; Linda Daou; Dina Roumieh (Perinatal Medicine Foundation, 2022)
Objective: Prenatal diagnosis of Galen vein aneurysm using color Doppler has become relatively easy. Management and timing of delivery is however challenging because of cardiac function deterioration. Ultrasound follow-up is essential to detect signs of fetal cardiac failure which must be weighed against risks of prematurity. Postnatal deterioration of the vital signs can follow a short period of improvement after birth. This report illustrates the many pitfalls that could affect the final outcome, raising the issue of the proper timing for delivery. Case(s): A 23-year-old G1P0 spontaneous pregnancy was referred at 28 WA for a Galen Vein aneurysm. The ultrasound finding included a 35 by 14 mm vascular structure with a turbulent flow, occupying the central part of the head. After 48 hours in-hospital surveillance through non-stress tests twice daily, she had a cesarean section due to a persistent non-reactive fetal heart rate, with absent variability. Unfortunately, despite a stable state for the first ten days, the baby's cardiac function deteriorated abruptly on day 11, and the baby died of heart failure despite medical management. Conclusion: The timing of delivery in cases with Galen vein aneurysm is challenging mainly in the case of premature babies, as the prognosis is globally bad. Postnatal deterioration of the vital signs can follow a short period of improvement after delivery.